An Analysis of Regulative Speech Acts in English Contracts - Qualitative and Quantitative Methods - Blom, Bjarne; Trosborg, Anna (HERMES - Journal of Language and Communication in Business, 1992)
This paper deals with the language used to express legal speech acts in simple contracts within the field of English Contract Law. The central objects of study are regulative functions, i.e. directive and commissive speech acts with a particular view to establishing realisation patterns of these rhetorical functions. The hypothesis that the speech acts subjecte to analysis are homogeneously distributed linguistic realisations typical for simple contracts is tested by means of partly manual analysis, partly machine-based quantification of the data of investigation. The findings show that statistically significant items are distributed homogenously in the corpus examined, and that the choice of individual strategies can be interpreted in terms of the face redress required by the socio-pragmatic situation.